Pengaruh Influencer Dan Social Media Sebagai Strategi Marketing Baba Rafi Enterprise Terhadap Keputusan Pembelian Produk Ngikan Dengan Brand Awareness Sebagai Variabel Moderating - Virgo Simamora; Riska Aulia Umry (JOURNAL FOR BUSINESS AND ENTREPRENEURSHIP, 2020)
This study aims to examine the influence of Influencers and Social Media as Baba Rafi Enterprise's Marketing Strategy on Ngikan Product Purchase Decisions with Brand Awarness as Moderating Variables. The population in this study are consumers ngikan products. The data collection technique was carried out by purposive sampling by distributing questionnaires to 100 respondents of Ngikan consumers using partial least square (PLS) data analysis. Based on statistical tests, The results showed that influencers had a significant effect on Ngikan Product Purchase Decisions, Social Media did not significantly influence Ngikan Product Purchasing Decisions, Brand Awareness had a significant effect on Ngikan Product Purchase Decisions. Moderation of Brand Awareness has insignificant effect and weakens the influence of Influencers on Ngikan Product Purchase Decisions. Brand Awareness moderation has a significant effect and has the character of strengthening the influence of Social Media on the Ngikan Product Purchase Decision. Kata Kunci : Brand Awareness, Influencer, Purchase Decisions, Social Media, Baba Rafi Enterprise’s Marketing Strategy